KONSISTENSI ALLAH DALAM DINAMIKA PERUBAHAN PERJANJIAN: ANALISIS TAFSIR TEOLOGIS ATAS KONSEP “BERIT” DAN “DIATHEKE” DALAM ALKITAB - Alex Rangan; Presdioyono; Andri Pasang; Delvin Siri'; Vricha (CV. ADIBA AISHA AMIRA, 2025)
This article examines God's consistency in the dynamics of covenant change by examining the concepts of berit in the Hebrew tradition and diatheke in the context of the New Testament. Through a theological exegetical approach that combines historical, linguistic, and narrative analysis, this study demonstrates that changes in the form, purpose, and expression of the covenant do not signal a change in God's character, but rather affirm His faithfulness in salvation history. Berit presents the relational foundation between God and people, where God's initiative and commitment are central. Meanwhile, the development of diatheke in Christ demonstrates the ultimate fulfillment of God's promise, paving the way for a new covenant that is universal, transformational, and rooted in grace. This article also highlights theological implications for contemporary believers, including understandings of faith identity, ethical life, and the ecclesiastical responsibility as a covenant community. Overall, this study confirms that God's consistency is fundamental to the reinterpretation of the covenant in the contemporary context, while also providing direction for a relevant and responsible life of faith.